Intervensi Diagnosis Komunitas dalam Upaya Menurunkan Kasus Baru Stunting di Desa Legok, Kabupaten Tangerang - Nadhira Rachma Kamila; Wynne Pratiwi; Tomi Wijaya; Emia Debora P; Silviana Tirtasari (Malahayati Nursing Journal, 2026)
ABSTRACT Stunting is a condition in which a child's height is below the standard for their age due to chronic nutritional deficiencies. In Indonesia, stunting remains a major health problem, with a prevalence of 21.5% in 2023, which is still far from the national target of 14% in 2024. In May 2025, the Legok Community Health Center recorded 60 new cases of stunting, with the highest number of new cases in Legok Village, highlighting the need for community diagnosis to understand the underlying causes and design more appropriate preventive measures. This program involves mothers of children under five through continuous improvement of their knowledge and skills in stunting prevention. The diagnosis process begins with the identification of various health problems, followed by prioritization using the USG (Urgency, Seriousness, Growth) method to determine the main problems that need to be addressed immediately To determine the contributing factors using the Blum Paradigm, prioritization using the non-scoring Delphi method, and searching for the root causes using Fishbone diagrams and 5 WHY analysis. Interventions were monitored using the PDCA (Plan-Do-Check-Act) cycle and evaluated using a systems approach. Interventions took the form of education about stunting, as demonstrated by 80% of participants obtaining a post-test score 80. These results show the importance of health promotion efforts in preventing stunting. Keywords:Community Diagnosis, Health Education, Health Promotion, Stunting.  ABSTRAK Stunting adalah kondisi ketika tinggi badan anak dibawah standar sesuai usianya akibat kekurangan gizi kronik. Di Indonesia stunting masih menjadi masalah kesehatan utama, prevalensi stunting pada tahun 2023 mencapai 21,5% yang masih jauh dari target nasional yaitu 14% pada tahun 2024. Pada Mei 2025, Puskesmas Legok mencatat 60 kasus baru stunting, dengan kasus baru tertinggi di Desa Legok, sehingga perlunya diagnosis komunitas untuk memahami penyebab dasar dan merancang langkah pencegahan yang lebih tepat.  Program ini melibatkan para ibu balita melalui peningkatan pengetahuan dan ketrampilan dalam pencegahan stunting secara berkesinambungan. Proses diagnosis dimulai dengan identifikasi berbagai masalah kesehatan, kemudian dilanjutkan dengan penentuan prioritas menggunakan metode USG (Urgency, Seriousness, Growth) untuk menentukan masalah utama yang perlu segera ditangani. Identifikasi masalah penyebab dengan Paradigma Blum, penentuan prioritas dengan metode Delphi non-scoring, dan mencari akar masalah penyebab  dengan diagram Fishbone dan analisis 5 WHY. Intervensi dimonitor menggunakan siklus PDCA (Plan-Do-Check-Act) dan dievaluasi dengan pendekatan sistem. Intervensi berupa edukasi mengenai stunting, ditunjukkan dengan  80% peserta memperoleh nilai post-test 80. Hasil ini menunjukkan bahwa pentingnya upaya promotif kesehatan dalam pencegahan stunting.  Kata Kunci: Diagnosis komunitas, Edukasi Kesehatan, Upaya promotif, Stunting.